If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + -9) = 7x + -9 Reorder the terms: 6(-9 + x) = 7x + -9 (-9 * 6 + x * 6) = 7x + -9 (-54 + 6x) = 7x + -9 Reorder the terms: -54 + 6x = -9 + 7x Solving -54 + 6x = -9 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -54 + 6x + -7x = -9 + 7x + -7x Combine like terms: 6x + -7x = -1x -54 + -1x = -9 + 7x + -7x Combine like terms: 7x + -7x = 0 -54 + -1x = -9 + 0 -54 + -1x = -9 Add '54' to each side of the equation. -54 + 54 + -1x = -9 + 54 Combine like terms: -54 + 54 = 0 0 + -1x = -9 + 54 -1x = -9 + 54 Combine like terms: -9 + 54 = 45 -1x = 45 Divide each side by '-1'. x = -45 Simplifying x = -45
| 5(x-4)+3(x-4)=0 | | 4y+12=9x | | c+ax=dx | | 57=35x | | t=0 | | 8+7x-x^2= | | 5x-3=7x-3x | | 3x^3+15x^2-18x= | | 14-(x+6)=5x-4 | | 3.5=7s | | 3x-4=24x+10 | | -16+5n=-.5(-6+8n)+3 | | -(8y+5)-(-7y-8)=-3 | | 5(3x-2)+5x-7=16+2x | | (x-1)=(x-3)(x-4) | | x^5+2x^4-35x^3= | | 3(x-5)+2=2(x-4) | | 8y-9(4y-11)= | | 8x-(5-x)=2*(x-3)+7x+1 | | lnx^9=lnx^2+18 | | lnx^8=lnx^2+18 | | -7x^2+12x+27= | | w^2+6w-432=0 | | 5y+10-2y=4+2y+2 | | 2x^2-30x-12=0 | | 9n^2+40n+49= | | 3(t-4)=5t | | 5y-7y=11 | | 21x^3-91x^2-70x= | | 6(2x-3)=3x-2x | | x^2-0.018x-0.063=0 | | 3x-5=2(1-2x) |